Taming the polysulphide shuttle in Li–S batteries by plasma-induced asymmetric functionalisation of the separator1. Issue 97 (21st October 2015) - Conder, Joanna; Urbonaite, Sigita; Streich, Daniel; Novák, Petr; Gubler, Lorenz
<x xml:space="preserve">Abstract</x> A novel polymer separator in the form of an asymmetric porous membrane with grafted Li+ exchange groups demonstrated superior polysulphide rejection ability and improved coulombic efficiency in comparison to the standard Celgard separator.